Implikasi Psikologis Pelaksanaan Ngaben Terhadap Sradha dan Bhakti Umat Hindu - Ni Made Ayu Erna Tanuria Sari (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Philosophically, the meaning of Ngaben Ceremony performed by the community in general, including the Mass Ngaben Ceremony is as a process to accelerate the return of elements of Panca Maha Bhuta to its origin or to their respective sources. The Ngaben ceremony also hasthe meaning of assisting Atman’s journey towards Brahman. With the return of Panca Maha Bhuta elements forming Sthula Sarira, Atman has increased his journey from Bhur Loka to Bhuwah Loka. In Bhuwah Loka Atman is still dressed Suksma Sarira. Thus the Ngaben ceremonyis the first stage of purification of Pitara, by releasing Pitara from the Panca Maha Bhuta ties. Sometimes in the community there is an understanding that is less in line with religious literature, about the nature and purpose of the Ngaben ceremony. Often the implementation of Ngaben is mistakenly interpreted, namely to find the place of the spirits of his ancestors in Heaven. In the course of the ancestral spirits to heaven, it requires a lot of provisions or beya in the form of a great banten.Keywords: Psychological Implication, Ngaben, Sradha, Bhakti